2010
DOI: 10.5688/aj740584
|View full text |Cite
|
Sign up to set email alerts
|

Patient-oriented Personality Traits of First-year Pharmacy Students

Abstract: Objective. To determine, using the Gordon Personal Profile-Inventory (GPP-I), if the personality traits of first-year pharmacy students match the traits required for patient-centered practice. Methods. The GPP-I, which measures the personality traits of ascendency, responsibility, emotional stability, sociability, cautiousness, original thinking, personal relations, and vigor, was administered to incoming pharmacy students at the beginning of their first semester. Results. The pharmacy school had attracted stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The authors broadly suggest that studying personality may help in understanding why pharmacists take up advanced pharmacy practice roles and may facilitate the design of interventions to foster innovation and practice change to promote activation of these traits . In the context of pharmacy students, personality traits have also been suggested as a tool for admission criteria for entry into pharmacy schools or targets for enhancement through appropriate academic learning and professional socialisation . In the medical profession, personality traits have been proposed as a tool for the recruitment and retainment of rural doctors, the design of environments to enhance patient satisfaction, the selection of surgical versus non‐surgical residents and as a way to predict job satisfaction in trauma surgeons,…”
Section: Discussionmentioning
confidence: 99%
“…The authors broadly suggest that studying personality may help in understanding why pharmacists take up advanced pharmacy practice roles and may facilitate the design of interventions to foster innovation and practice change to promote activation of these traits . In the context of pharmacy students, personality traits have also been suggested as a tool for admission criteria for entry into pharmacy schools or targets for enhancement through appropriate academic learning and professional socialisation . In the medical profession, personality traits have been proposed as a tool for the recruitment and retainment of rural doctors, the design of environments to enhance patient satisfaction, the selection of surgical versus non‐surgical residents and as a way to predict job satisfaction in trauma surgeons,…”
Section: Discussionmentioning
confidence: 99%
“…10 The GPP-I has been used in various other papers related to personality traits of pharmacists, pharmacy and medical students. 15 , 25 , 26 , 27…”
Section: Methodsmentioning
confidence: 99%
“…14 Previous studies by the authors found that first year pharmacy students were characterised by strong traits of Original Thinking, Personal Relations and Vigor, however they had low scores on assertiveness. 15 …”
Section: Introductionmentioning
confidence: 99%
“…12 The pharmacy education literature has highlighted work that focuses on the self-development of students related to discovery of personality, emotional intelligence, talents, and strengths. 9,[37][38][39] Disciplines outside the profession have described personal growth projects and other mechanisms to encourage a student's focus on their own self-development. 40 Guiding Principle 4: Leadership development should take place in a wide variety of settings including didactic curriculum, experiential curriculum, and extracurricular involvement.…”
Section: Fundamental Preceptsmentioning
confidence: 99%